2022
DOI: 10.2166/nh.2022.136
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of runoff variation to climate and human-driven changes in the transition zone between the Qinling Mountains and the Loess Plateau under vegetation greening

Abstract: The need for water safety management has increased in the transition zone between the Qinling Mountains and the Loess Plateau, China due to streamflow decline over the past 30 years. Vegetation greening, largely due to the result of the ‘Grain for Green’ program implemented in the Loess Plateau, is affecting regional streamflow together with climate change and direct human impacts. There is thus an urgent need to evaluate the relative importance of causes of streamflow variation in this region. A Hydrological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In arid regions, vegetation greening might lead to a series of negative ecohydrological effects in watersheds, such as reduced river runoff, insufficient ecological water demand, soil salinization, and reduced species diversity [18,19]. Wu et al [20] found that the main cause of runoff attenuation in the transition zone between the Qinling Mountains and the Loess Plateau was vegetation greening. In water-limited regions, changes in evapotranspiration and runoff due to vegetation greening are notably larger than in energy-limited regions; thus, the phenomenon of vegetation greening in arid zones can exacerbate water scarcity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In arid regions, vegetation greening might lead to a series of negative ecohydrological effects in watersheds, such as reduced river runoff, insufficient ecological water demand, soil salinization, and reduced species diversity [18,19]. Wu et al [20] found that the main cause of runoff attenuation in the transition zone between the Qinling Mountains and the Loess Plateau was vegetation greening. In water-limited regions, changes in evapotranspiration and runoff due to vegetation greening are notably larger than in energy-limited regions; thus, the phenomenon of vegetation greening in arid zones can exacerbate water scarcity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These impacts can be categorized as direct (e.g., water use and reservoir construction) or indirect (e.g., changes in land use patterns) [22]. In recent years, human activities on the Loess Plateau mainly affect runoff indirectly [25][26][27]. The underlying surface, particularly the vegetation coverage, has undergone changes due to human activities in the Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%